Proximity Always Matters: Local Bias When the Set of Local Companies Changes - Bodnaruk, Andriy (Review of Finance, 2009)
Abstract I analyze the portfolios of individual investors who have changed their place of residence. As distance from a company they invest in changes, investors adjust their portfolio composition. The farther investors move away from the closest establishment of a company in their portfolio, the more of its shares they sell compared to investors who do not move. Among the companies that investors held before the move, after moving, investors abnormally increase their ownership in companies closer to their new location; these companies provide them with higher risk-adjusted returns than companies in which they kept holdings unchanged or abnormally reduced holdings.